Pengembangan Keterampilan Pembacaan Maulid Dan Seni Hadrah Al-Banjari Bagi Remaja Masjid Darul Mu’awanah Banjaranyar Tanjunganom Nganjuk - Afiful Huda; Ahmad Mustakim; Abdul Jalil Jawhari (LP3M STAI Darussalam Krempyang Nganjuk, 2021)
Nowadays, youth is an important asset for the next generation of Nation and Religion, but it should be noted that there are so many disturbances that usually come at any time, one of which is technology. The youth of the Masjid Dusun Banjaranyar mostly have religious education experience a sluggishness in activities, because the mosque, which is supposed to be the center of education, is not given much attention, and there are rarely activities or even none. We focus on this program in developing Hadroh Arts skills and reading Mawlid, this activity involves mosque youth and youth youth organizations. This program is pursued through several stages, namely: Appreciative Inquiry (AI); Discovery; Visioning; Asset Mapping; Mobilization (Action Planning), Monitoring and Evaluation. The method used is service learning, including learning strategies, teaching, and reflecting. The result of this service is the impact of changes from each participant, this can be seen from the results of the pre-test and post-test assessments carried out. Changes from each participant began to improve a lot, this was also seen after conducting a posttest assessment with routine exercise twice a week, everything became more evenly distributed.